2020
DOI: 10.1371/journal.pone.0229790
|View full text |Cite
|
Sign up to set email alerts
|

The global scientific research response to the public health emergency of Zika virus infection

Abstract: BackgroundScience studies have been a field of research for different knowledge areas, and they have been successfully used to analyse the construction of scientific knowledge, practice and dissemination. In this study, we aimed to verify how the Zika epidemic has moulded the scientific articles published worldwide by analysing international collaborations and the knowledge landscape through time, as well as research topics and country involvement. OPEN ACCESS Citation: Oliveira JFd, Pescarini JM, Rodrigues Md… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
4
18
0
2
Order By: Relevance
“…The short-term effect of research efforts of earlier CoV research and the strengthening of international networking could also be shown with regard to another emerging virus epidemic that occurred in South America in 2015: the Zika virus infection. The publication patterns corresponded to those reported here and showed an unsustainable short-term effect of national and international efforts [ 30 ]. This similar publication pattern was reinforced by the enormous research incentives of short-term funding and public recognition due to the acute threat.…”
Section: Discussionsupporting
confidence: 83%
“…The short-term effect of research efforts of earlier CoV research and the strengthening of international networking could also be shown with regard to another emerging virus epidemic that occurred in South America in 2015: the Zika virus infection. The publication patterns corresponded to those reported here and showed an unsustainable short-term effect of national and international efforts [ 30 ]. This similar publication pattern was reinforced by the enormous research incentives of short-term funding and public recognition due to the acute threat.…”
Section: Discussionsupporting
confidence: 83%
“…Our results highlighted the importance of gathering public interest in global health issues, and how public interest can act as a powerful catalyzer to trigger the research eld (30,31). Likewise, we found that the efforts to overcome the global emergency caused by the ZIKV outbreak in the Americas led to globalization in the research eld (32).…”
Section: Discussionsupporting
confidence: 59%
“…In 1947, in the Zika forest of Uganda, ZIKV was primarily identi ed in a sentinel rhesus monkey and was rst detected in humans in 1952. In 2014, the virus quickly spread into the Americas and in 2016, the World Health Organization (WHO) declared ZIKV epidemic as a public health emergency [17,[19][20][21]. Considerable scienti c efforts resulted in many candidate vaccines that are currently undergoing further clinical development.…”
Section: Introductionmentioning
confidence: 99%